What We Talk About When We Talk About Inequality: An Introduction to the Journal of Management Studies Special Issue - Suddaby, Roy; Bruton, Garry D.; Walsh, James P. (Journal of Management Studies, 2018)
This introduction to the Journal of Management Studies Special Issue on Inequality argues that the way we frame conversations about inequality reveals important information about how poverty and inequality have become institutionalized in modern society. We observe a distinct recent shift in the collective conversation about vulnerable populations in western society away from poverty and toward inequality. We question why this shift has occurred and who benefits from it. Drawing from the provocative papers that populate the Special Issue we describe how forms of talk can help create inequality, maintain it and holds the potential to change it. We encourage new research that adopts a holistic reintegration of poverty and inequality by attending to the ‘dirty realism’ of the violence of poverty and the dire consequences of internalized inequality.